The Use of Some Inorganic Additives to Retard Combustion and Flammabitity of Unsaturated Polyester and Epoxy Resins - Ugal, J. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, three inorganic additives were 1,1sed, these are (I) ; tetraethyl ammonium bromodichloro phenylphsphin, (II) Chlorinated paraffine. and (ITI) a mixture of (50% by weight of each) to study the synergetic effect. These additives \’vÂ·cre used as flame retardants with unsaturated polyester and epoxy resins.;, since these resins are industrially important and of uses in life. Results showed efficiency of these additives to retard fl mmabillty and stop burning of resins throqght the ASTM tests used Measurement of Limiting oxygen index (LOI), rate of burning (R.B), average extent of burning (AEB).. av rage time of l;mrning ATB) and the height of flame (H), had been d:one. The activity of the additive.s was according to the following order: HI> I>ll Depending on their composition and. thermal decomposition during burning.